2020
DOI: 10.3390/v12030318
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Rotavirus A in Raw Sewage Samples from Northeast Spain

Abstract: Rotavirus A (RVA) is the most common virus associated with infantile gastroenteritis worldwide, being a public health threat, as it is excreted in large amounts in stool and can persist in the environment for extended periods. In this study, we performed the detection of RVA and human adenovirus (HAdV) by TaqMan qPCR and assessed the circulation of RVA genotypes in three wastewater treatment plants (WWTPs) between 2015 and 2016 in Catalonia, Spain. RVA was detected in 90% and HAdV in 100% of the WWTP samples, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 37 publications
(53 reference statements)
1
13
0
Order By: Relevance
“…All samples were positive for our internal control, bacteriophage MS2, although with variable efficiency (33.3 % ± 15.6). Such a variation has been described before (Petterson et al, 2015;Silva-Sales et al, 2020), probably due to the complexity and variability of sewage samples.…”
Section: Resultsmentioning
confidence: 60%
“…All samples were positive for our internal control, bacteriophage MS2, although with variable efficiency (33.3 % ± 15.6). Such a variation has been described before (Petterson et al, 2015;Silva-Sales et al, 2020), probably due to the complexity and variability of sewage samples.…”
Section: Resultsmentioning
confidence: 60%
“…A total of 40 samples from Rajasthan and 14 samples from Uttarakhand collected between May 4 and August 14 (2020) were tested for the presence of SARS-CoV-2 RNA. Some variations in Ct values are probably due to the complexity and variability of the sewage samples and has been described before [29,30]. The interpretation of results in Table 3 (from different sites, as described in Table 1) was based on categorizing a sample as positive when the cycle threshold took place below cycle 40, for either two of the three genes such as RNA-dependent polymerase (RdRP), nucleocapsid (N) SARS-CoV-2 specific genes and gene E, characteristic of pan-Sarbeco viruses detection, as per manufacturer's instructions.…”
Section: Detection Of Sars-cov-2 Rna In Untreated Wastewater Samplesmentioning
confidence: 81%
“…A study conducted between 2015 and 2016 revealed the presence of RVA in high viral loads in sewage samples from Barcelona. The authors also found no evidence of RVA vaccine-related strains in the sewage samples [ 74 ]. These results suggest that RVA is widespread in the community, since the population excretes RVA and the children still require healthcare assistance due to gastroenteritis associated with RVA.…”
Section: Resultsmentioning
confidence: 99%